From consultation to co-production: high-involvement change - Garrow, Valerie (Brighton, 2016)
"High-involvement work practices have featured in management research and literature for decades but when it comes to organisational change, people still tend to feel 'done to'. This might be because change is often happening in crisis mode when things need to happen quickly and control is centralised. There is usually some form of consultation but little real involvement in the design and development of structures and processes that will impact people's working lives. Organisational change expert, Valerie Garrow, highlights that for most of the last century leaders have been ignoring research on the benefits of employee involvement, which helps to explain the continuing high failure rates of the planned 'transformations' in organisations. Yet, as she describes, current technologies and conditions provide new opportunities for high-involvement change and to move from 'consultation to co-creation."